Comparative Study of Physico- chemical Parameters of Ground water of Residential and Industrial area of Sirgitti in Bilaspur District - Patel, Rajani; Nayar, Renu; Patel, Kavita; Tandon, Sandeep Kumar (International Journal of Membrane Science and Technology, 2023)
Water is available in abundance on the earth. It is one of the main reasons which make life possible on our planet. The quality strength and type of sewage depends upon the human population, industrialization, deforestation and life style of people. Analytical explorations of some selected physico- chemical parameter have been made on the ground water bodies of Sirgitti industrial area. In the present comparative study for physico-chemical analysis water samples were collected from to different locations the residential and industrial area of Sirgitti in Bilaspur district. The laboratory test of the collected water samples were performed for analysis of some selected physico-chemical parameters such as pH, EC, TDS, DO, COD, Total hardness, Fluoride, chloride etc. The methods employed for the analysis as per standard methods recommended by APHA and WHO standard of drinking water. The obtained values are compared with the standard limit. The results of this study reveals that in the industrial area of the physico-chemical parameters higher in the maximum permissible limit of WHO with variations in some parameters. Both the sampling stations groundwater unsuitable for domestic, irrigation and drinking purposes but the industrial area of BEC fertilizers groundwater is more polluted than the Adarsh nagar residential area of Sirgitti. So it is essential that the quality of ground water should be regular checked and also needs treatment before direct use.